‘Don't ask, don't tell’ Ethical issues concerning and learning and maintaining life-saving skills - Gboyega A. Ogunbanjo; Donna Knapp van Bogaert (South African Family Practice)
Undergraduate and postgraduate medical education entails acquiring and maintaining technical skills of various natures. Peripheral venous cannulation, splinting of fracture, wound suturing, venous cut-down and intra-osseous catheter placement for the most part, are considered minimally invasive procedures. The traditional way of skill acquisition could be summarised by the adage “See one, do one, teach one”. Although the saying may be a misrepresentation of the reality, it should not be an optional educational approach. Patients undergoing a procedure under general anaesthesia are often not informed of the possibility that they could be used for “ghost procedures”- part or whole of the procedure is performed by a trainee. An attitude of “don't ask, don't tell” devalues patients' autonomy and the trainee's moral integrity. In view of the polarisation of the views about teaching, acquiring, and maintaining technical skills, institutions should consider and deliberate on these principles and reach consensus on a set of guidelines to clarify and limit the practice of learning technical skills on patients and on the newly dead. Informed consent procedures and requirements must be clearly established and communicated. The learning and proficiency practices should be restricted to the staff that can truly benefit from the experience. The practice of ‘don't ask, don't tell’ is not an option.